Composite aerogel insulation board as well as preparation method and application thereof
By using composite aerogel felt and metal plate design in the aerogel insulation board, combined with specific additives in the modification liquid, a network connection structure is formed, and the problem of insufficient mechanical properties of the aerogel insulation board is solved, and the problem of achieving the goal of achieving It has better thermal insulation and mechanical properties, and is suitable for high-demand application scenarios.
Patent Information
- Application Number
- CN202411460966.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing aerogel insulation boards have poor mechanical properties, which limits their application in areas with high insulation performance requirements.
The composite aerogel insulation board is designed, including substrate, composite aerogel felt and metal plate. The composite aerogel felt consists of silica aerogel felt, polyimide aerogel foam layer and glass fibers. , the network connection structure is formed by adding additives such as graphene oxide, PAMAM, carboxylated multi-walled carbon nanotubes and 1,3,5-triaminobenzene in the modification solution to enhance mechanical strength and thermal stability.
It significantly improves the mechanical strength and thermal stability of composite aerogel felt, enhances the insulation effect, and improves the stability and mechanical properties of the overall structure. It is suitable for high-demand construction, aerospace and other fields.
Smart Images

Figure BDA0005091855090000101 
Figure BDA0005091855090000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermal insulation materials, and more specifically, to a composite aerogel thermal insulation board and a preparation method and application thereof. Background Art
[0002] At present, thermal insulation materials are widely used in the fields of construction, transportation, aerospace, etc. Commonly used thermal insulation materials include organic materials such as polystyrene and polyurethane, and inorganic materials such as silicate and glass fiber. Although these traditional organic or inorganic thermal insulation materials have certain thermal insulation effects, they are insufficient in thermal insulation performance and mechanical strength. The above defects limit the application of thermal insulation boards in a wider range of fields, especially in occasions with extremely high requirements for thermal insulation performance.
[0003] The structural feature of aerogel is a highly permeable cylindrical multi-branched nanoporous three-dimensional network structure with a porosity of more than 80%. It has an extremely high porosity and an extremely low density, and has an extremely low thermal conductivity coefficient. The thermal conductivity is extremely low, which is usually much lower than traditional thermal insulation materials such as polystyrene boards, glass wool, etc., so it has excellent thermal insulation effects; and due to the chemical stability of the aerogel material in this application, it also has good thermal insulation properties. At the same time, the aerogel also has an ultra-light weight, which reduces the construction load. Therefore, aerogel has broad application prospects in thermal insulation materials.
[0004] However, the mechanical properties of ordinary aerogel insulation boards are poor, which limits their application development. Therefore, the preparation of composite aerogel insulation boards with better comprehensive thermal insulation and mechanical strength properties is of great significance to the development and application of aerogel insulation boards. Summary of the invention
[0005] In order to improve the mechanical strength of an aerogel insulation board and obtain a composite aerogel insulation board with better comprehensive thermal insulation and mechanical strength performance, the present application provides a composite aerogel insulation board and a preparation method and application thereof.
[0006] In a first aspect, the present application provides a composite aerogel insulation board, which adopts the following technical solution: A composite aerogel insulation board comprises a substrate and metal plates arranged on both sides of the substrate, a composite aerogel felt is arranged between the substrate and the metal plate, and the composite aerogel felt is prepared by the following method: The silica aerogel felt is immersed in a modified liquid, dried, and then sprinkled with glass fiber, and then bonded with a polyimide aerogel foam layer, wherein the polyimide aerogel foam layer is bonded to a substrate, and the silica aerogel felt is bonded to a metal plate; Among them, the modified liquid mainly includes graphene oxide, PAMAM, carboxylated multi-walled carbon nanotubes, 1,3,5-triaminobenzene and genipin.
[0007] By adopting the above technical scheme, the composite aerogel insulation board in the present application includes a substrate, a composite aerogel felt and a metal plate. This structural design not only enhances the overall strength of the insulation board, but also improves the heat reflection performance of the metal plates on both sides of the substrate, which helps to further improve the thermal insulation effect. More importantly, the composite aerogel felt in the present application includes a silica aerogel felt, a polyimide aerogel foam layer and glass fibers arranged therebetween. The polyimide aerogel is a three-dimensional porous material cross-linked by polymer molecular chains. Compared with the silica inorganic aerogel with poor mechanical properties, the polyimide aerogel has the characteristics of low thermal conductivity and high specific surface area. In addition, the polyimide aerogel has the characteristics of high mechanical properties, high thermal stability and extremely low thermal conductivity. Therefore, the composite gel felt in the present application uses a composite of silica aerogel felt and polyimide aerogel foam layer, which can achieve better thermal insulation effect and mechanical properties, and the glass fibers spread between the two can play a certain reinforcing role. Moreover, in the present application, the glass fiber is located between the silica aerogel felt and the polyimide aerogel foam layer, and can form a needle-punched structure with the two, which is more conducive to improving the bonding strength between the two, thereby improving the stability and mechanical properties of the overall structure. In addition, the silica aerogel felt is first immersed in a modifying liquid, and the addition of graphene oxide and carboxylated multi-walled carbon nanotubes in the modifying liquid further plays a reinforcing role. More importantly, the surface of the silica aerogel contains silicon hydroxyl groups, and the surface of the graphene oxide contains hydroxyl and carboxyl functional groups. The addition of PAMAM (polyamide-amine dendrimer) allows the amino groups thereon to form chemical bonds with the hydroxyl groups on the surface of the silica aerogel, the carboxyl and hydroxyl groups on the surface of the graphene oxide, and the carboxyl oxygen-containing functional groups on the surface of the carboxylated multi-walled carbon nanotubes. Combined with the addition of 1,3,5-triaminobenzene, the three amino groups and the benzene ring structure in its molecular structure have strong intermolecular forces. The amino groups on its molecular structure and the amino groups in the PAMAM molecular structure can not only form covalent bonds with the hydroxyl and carboxyl groups on graphene oxide, carboxylated multi-walled carbon nanotubes and silica aerogels, but also form covalent bonds with the hydroxyl groups in glass fibers and the carboxyl and amide functional groups on the polyimide molecular chains, and then cooperate with genipin to realize the connection between the amino groups, thereby forming a network connection structure between the silica aerogel felt and the modified liquid, glass fiber and polyimide aerogel foam layer, which not only helps to enhance the silica aerogel structure to form a more uniform and dense microscopic connection structure, but also helps to improve the overall mechanical strength and thermal stability of the composite aerogel felt, better maintain the network structure of the aerogel, and prevent the thermal insulation performance from decreasing due to thermal decomposition or thermal shrinkage. Moreover, the formed macromolecular network structure cooperates with the dispersion of carbon fibers and graphene oxide to significantly improve the mechanical properties of the overall composite aerogel felt.
[0008] Optionally, the modified liquid includes the following raw materials in parts by weight: 8-15 parts of polyvinyl alcohol, 5-10 parts of polyacrylamide, 30-40 parts of water, 10-20 parts of graphene oxide, 5-15 parts of PAMAM, 15-25 parts of carboxylated multi-walled carbon nanotubes, 3-8 parts of 1,3,5-triaminobenzene, 1-3 parts of genipin, 10-20 parts of ethanol and 2-5 parts of Sodium carboxymethyl cellulose.
[0009] By adopting the above technical solution, the addition of graphene oxide and carboxylated multi-walled carbon nanotubes plays a reinforcing role, the above reinforcing fillers form a suspension in the solvent system, and the addition of sodium carboxymethyl cellulose prevents the above fillers from settling in the solvent, so that they can be more evenly loaded inside and on the surface of the silica aerogel felt during the impregnation process.
[0010] Optionally, when the silica aerogel felt is immersed in the modified liquid, the immersion temperature is 40-50° C., the immersion time is 40-60 min, and the immersion pressure is 1.2-2.5 MPa.
[0011] By adopting the above technical solution, when the silica aerogel is immersed in the modifying liquid, applying a certain temperature and pressure is more conducive to forming a chemical connection between the modifying liquid and the silica aerogel felt, thereby achieving the modification of the silica aerogel felt.
[0012] Optionally, the thickness of the silica aerogel felt is 3-5 mm, and the thickness of the polyimide aerogel foam layer is 1-2 mm.
[0013] By adopting the above technical solution and controlling the thickness of the polyimide aerogel foam layer, the polyimide aerogel foam layer can be matched with the silica aerogel felt to have better thermal insulation effect and better mechanical properties.
[0014] Optionally, the polyimide aerogel foam layer is first immersed in an impregnation liquid and then dried and composited with a silica aerogel felt, wherein the impregnation liquid comprises the following raw materials in parts by weight: 5-10 parts of porous tin dioxide-wood ceramic powder composite particles, 2-5 parts of polyetheretherketone particles, 3-5 parts of sodium carboxymethyl cellulose and 20-30 parts of water.
[0015] By adopting the above technical scheme, the wood ceramic powder is obtained by modifying the silicon carbide ceramic precursor polycarbosilane to obtain the wood ceramic powder, and then compounding it with porous tin dioxide to obtain composite particles. The strong mechanical properties of silicon carbide ceramics are utilized, and the fine porous structure of wood is matched, and it is loaded in the porous tin dioxide and added. The porous tin dioxide also has excellent mechanical properties. Combined with the high strength and high temperature resistance of polyetheretherketone Peek particles, when the polyimide aerogel foam is impregnated in the above impregnation solution, the above composite particles and polyetheretherketone particles are loaded on the polyimide aerogel foam layer, which significantly improves the mechanical properties of the foam layer, thereby significantly improving the mechanical properties of the composite aerogel felt layer. The aerogel insulation board finally obtained has excellent thermal insulation properties as well as excellent mechanical properties.
[0016] Optionally, the porous tin dioxide-wood ceramic powder composite particles are prepared by the following method: Heat polycarbosilane and xylene in a water bath at 70-85°C, add wood powder after stirring, and then impregnate for 40-60 minutes under a vacuum condition of -0.09-(-0.1). After the impregnation, add porous tin dioxide, stir, and then heat to 150-170°C, keep warm for 20-30 minutes, then heat to 230-250°C, keep warm for 30-40 minutes and then cool to obtain porous tin dioxide-wood ceramic powder composite particles.
[0017] By adopting the above technical scheme, in the present application, polycarbosilane is first impregnated with wood powder and xylene solvent under vacuum conditions, which helps the impregnation modification of polycarbosilane in wood powder and realizes the modification of wood powder on polycarbosilane. Then porous tin dioxide is added and stirred. During the heating process, wood ceramic powder is gradually generated, and the xylene solvent gradually evaporates. The temperature continues to rise to further realize the carbonization of the wood powder to form wood ceramic powder. In addition, part of the wood ceramic powder and the porous tin dioxide are mutually loaded. The mechanical properties of the metal oxide are combined with the partial ceramic properties of the loaded wood ceramic powder. It is found that the addition of the above composite particles can significantly improve the mechanical properties while also improving the thermal insulation properties to a certain extent.
[0018] Optionally, during the preparation of the porous tin dioxide-wood ceramic powder composite particles, the added amounts of the raw materials are as follows: 10-20 parts of polycarbosilane, 15-25 parts of xylene, 10-20 parts of wood powder, and 12-20 parts of porous tin dioxide.
[0019] Optionally, the spreading amount of the glass fiber is 3-5wt% of the mass of the silica aerogel felt.
[0020] Optionally, the substrate comprises the following raw materials in parts by weight: 40-60 parts of water, 80-120 parts of cement, 5-10 parts of silica aerogel powder, 5-8 parts of EVA emulsion, 3-8 parts of acrylic emulsion, 5-15 parts of expanded perlite, 20-30 parts of sand, 3-5 parts of glass fiber, 10-15 parts of limestone powder and 0.3-0.5 parts of water reducer.
[0021] By adopting the above technical scheme, the base material in the present application is mainly made of cement mortar, with acrylic emulsion and EVA emulsion added to improve waterproofness and adhesion, and the addition of glass fiber improves its crack resistance and mechanical properties. The final thermal insulation composite board has excellent performance.
[0022] In a second aspect, the present application provides a method for preparing a composite aerogel insulation board, which adopts the following technical solution: A method for preparing a composite aerogel insulation board comprises the following steps: S1, after the silica aerogel felt is immersed in a modified liquid, it is sprinkled with glass fiber, solidified, and then bonded and solidified with a polyimide aerogel foam layer to obtain a composite aerogel felt; S2. The polyimide aerogel foam layer side of the composite aerogel felt is bonded and cured with the substrate by adhesive, and the silica aerogel felt side of the composite aerogel felt is bonded and cured with the metal plate by adhesive to form a composite aerogel insulation board.
[0023] By adopting the above technical solution, the method provided by the present application is simple, convenient and easy to realize industrialization.
[0024] In a third aspect, the present application provides an application of a composite aerogel insulation board, using the following technical solution: an application of a composite aerogel insulation board in the fields of construction and aerospace.
[0025] In summary, this application has the following beneficial effects: 1. The composite aerogel felt in the present application includes a silica aerogel felt, a polyimide aerogel foam layer and a glass fiber arranged therebetween, which can achieve better thermal insulation and mechanical properties, and the glass fiber spread between the two can play a certain reinforcing role, and the glass fiber in the present application is between the silica aerogel felt and the polyimide aerogel foam layer, and can form a needle-punched structure with the two, which is more conducive to improving the bonding strength between the two, thereby improving the stability and mechanical properties of the overall structure; 2. The silica aerogel felt of the present application is first soaked in a modifying liquid. The addition of PAMAM and 1,3,5-triaminobenzene can form covalent bonds with the hydroxyl groups on the surface of the silica aerogel, the carboxyl and hydroxyl groups on the surface of graphene oxide, the hydroxyl groups in the glass fiber, and the carboxyl and amide functional groups on the polyimide molecular chain. Then, genipin is used to achieve the connection between the amino groups, thereby forming a network connection structure between the silica aerogel felt and the modifying liquid, the glass fiber and the polyimide aerogel foam layer. This not only helps to enhance the silica aerogel structure to form a more uniform and dense microscopic connection structure, but also helps to improve the overall mechanical strength and thermal stability of the composite aerogel felt, better maintain the network structure of the aerogel, and prevent the thermal insulation performance from decreasing due to thermal decomposition or thermal shrinkage. Moreover, the formed macromolecular network structure cooperates with the dispersion of carbon fiber and graphene oxide to significantly improve the mechanical properties of the overall composite aerogel felt. DETAILED DESCRIPTION
[0026] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0027] The polyimide aerogel foam layer in the following embodiments and preparation examples is obtained by cutting the polyimide PI ultra-short fiber aerogel foam board produced by Jiangxi Xiancai Nanofiber Technology Co., Ltd.; The silica aerogel felt is made by Guangdong Shuanghong Waterproof Insulation Engineering Co., Ltd., and its brand is Shuanghong. Its thermal conductivity is 0.017W / (m·K); The carboxyl multi-walled carbon nanotubes are selected from the carboxyl multi-walled carbon nanotubes of the brand BK and model CNT205 produced by Suzhou Kaifa New Material Technology Co., Ltd.; The silica aerogel powder is produced by Yinhuang (Shanghai) Industrial Co., Ltd., the brand is Cabot, the model is IC3100, and the particle size is 2-40μm. PAMAM uses the brand CYD-110A from Weihai Chenyuan Molecular New Materials Company, which contains 8 amino groups at the end; The porous tin dioxide can be commercially available. In the present application, the porous tin dioxide is prepared by the following method: Ethanol and water are mixed in a mass ratio of 1:8 to prepare a mixed solution, and then tin tetrachloride pentahydrate is added, stirred and dissolved to prepare a precursor solution, wherein the mass concentration of tin tetrachloride pentahydrate in the mixed solution is 35wt%; The precursor solution and 0.5 mol / L sodium hydroxide solution were mixed and heated to 50° C., with a volume ratio of the precursor solution to the sodium hydroxide solution of 1:1.5. The mixture was stirred for 20 min and then allowed to stand at a constant temperature. After aging for 25 h, a precipitate was crystallized to obtain a precipitate. The precipitate was filtered, washed, and dried to obtain a basic stannous chloride precursor. The prepared basic stannous chloride precursor was calcined in an air atmosphere at a temperature of 700° C. for 1.5 h, and then naturally cooled to room temperature to obtain porous tin dioxide.
[0028] The substrate in the present application is adaptively adjusted according to the application scenario of the insulation board, and can be a gypsum board or a metal board. For example, when it is used in building insulation materials, a cement gypsum board can be used.
[0029] The following preparation example is an example of the preparation of porous tin dioxide-wood ceramic powder composite particles Preparation Example 1 A method for preparing porous tin dioxide-wood ceramic powder composite particles comprises the following steps: 15g of polycarbosilane (Mw is 1400, available from Henan Weitixi Chemical Technology Co., Ltd.) and 20g of xylene are heated in a water bath at 80°C, and 15g of wood powder (wood powder formed after cutting the board) is added after stirring. Then, it is impregnated for 50 minutes under a vacuum degree of -0.05. After the impregnation, 15g of porous tin dioxide is added, stirred, and then the temperature is raised to 160°C. After keeping the temperature for 25 minutes, the temperature is raised to 240°C. After keeping the temperature for 35 minutes, it is cooled to obtain porous tin dioxide-wood ceramic powder composite particles.
[0030] Preparation Example 2 A method for preparing porous tin dioxide-wood ceramic powder composite particles comprises the following steps: 10g of polycarbosilane (Mw is 1400, available from Henan Weitixi Chemical Technology Co., Ltd.) and 15g of xylene are heated in a water bath at 70°C, stirred and then added with 10g of wood powder (wood powder formed after the board is cut), and then immersed for 60min under a vacuum degree of -0.09. After the immersion, 12g of porous tin dioxide is added, stirred, and then heated to 150°C, kept warm for 30min, then heated to 230°C, kept warm for 40min and then cooled to obtain porous tin dioxide-wood ceramic powder composite particles.
[0031] Preparation Example 3 A method for preparing porous tin dioxide-wood ceramic powder composite particles comprises the following steps: 20g of polycarbosilane (Mw is 1400, available from Henan Weitixi Chemical Technology Co., Ltd.) and 25g of xylene are heated in a water bath at 85°C, stirred, and then 20g of wood powder (wood powder formed after cutting the board) is added, and then immersed for 40 minutes under a vacuum degree of -0.1. After the impregnation, 20g of porous tin dioxide is added, stirred, and then the temperature is raised to 170°C, kept warm for 20 minutes, and then the temperature is raised to 250°C, kept warm for 30 minutes, and then cooled to obtain porous tin dioxide-wood ceramic powder composite particles.
[0032] Example 1 A method for preparing a composite aerogel insulation board comprises the following steps: S1. Specifically includes the following steps: S1-1, 35 kg of water and 15 kg of ethanol were mixed, and then 4 kg of sodium carboxymethyl cellulose was added, 6 kg of 1,3,5-triaminobenzene was added, and then 12 kg of polyvinyl alcohol, 8 kg of polyacrylamide, 15 kg of graphene oxide, 10 kg of PAMAM, 20 kg of carboxylated multi-walled carbon nanotubes, and 2 kg of genipin were added, and the mixture was stirred to obtain a modified solution; S1-2, immersing a 3 mm thick silica aerogel felt in a modified liquid at a temperature of 45°C, a immersion time of 50 min, and an immersion pressure of 2.0 MPa, then taking out the impregnated silica aerogel felt, and spreading glass fiber on one side of the silica aerogel felt, wherein the amount of the glass fiber is 4 wt% of the mass of the silica aerogel felt, and then drying and curing; S1-3, coating one side of the silica aerogel felt with glass fibers with an acrylic film, and then bonding and curing it with a polyimide aerogel foam layer with a thickness of 1.5 mm to obtain a composite aerogel felt; S2, bonding and curing the polyimide aerogel foam layer side of the composite aerogel felt and the substrate by adhesive, bonding and curing the silica aerogel felt side of the composite aerogel felt and the metal plate by adhesive, to form a composite aerogel insulation board, wherein the adhesive in step S2 is selected from acrylic self-adhesive glue; The substrate in step S2 is prepared by the following method: 50kg of water, 100kg of cement, 8kg of silica aerogel powder, 6kg of EVA emulsion, 5kg of acrylic emulsion, 10kg of expanded perlite, 25kg of sand, 4kg of glass fiber, 12kg of limestone powder and 0.4kg of water reducing agent were mixed evenly and put into a mold, pressed and cured to obtain a substrate.
[0033] Example 2 A method for preparing a composite aerogel insulation board comprises the following steps: S1. Specifically includes the following steps: S1-1, 30 kg of water and 10 kg of ethanol were mixed, and then 2 kg of sodium carboxymethyl cellulose was added, 3 kg of 1,3,5-triaminobenzene was added, and then 8 kg of polyvinyl alcohol, 5 kg of polyacrylamide, 10 kg of graphene oxide, 5 kg of PAMAM, 15 kg of carboxylated multi-walled carbon nanotubes, and 1 kg of genipin were added, and the mixture was stirred to obtain a modified solution; S1-2, immersing a 3 mm thick silica aerogel felt in a modified liquid at a temperature of 40°C, a time of 60 min, and a pressure of 1.2 MPa, then taking out the impregnated silica aerogel felt, and spreading glass fiber on one side of the silica aerogel felt, wherein the amount of the glass fiber is 3 wt% of the mass of the silica aerogel felt, and then drying and curing; S1-3, coating one side of the silica aerogel felt with glass fibers with an acrylic film, and then bonding and curing it with a polyimide aerogel foam layer with a thickness of 1 mm to obtain a composite aerogel felt; S2. The polyimide aerogel foam layer side of the composite aerogel felt is bonded and cured with the substrate by adhesive, and the silica aerogel felt side of the composite aerogel felt is bonded and cured with the metal plate by adhesive to form a composite aerogel insulation board, wherein the adhesive in step S2 is acrylic self-adhesive.
[0034] The substrate in step S2 is prepared by the following method: 40kg of water, 80kg of cement, 5kg of silica aerogel powder, 5kg of EVA emulsion, 3kg of acrylic emulsion, 5kg of expanded perlite, 20kg of sand, 3kg of glass fiber, 10kg of limestone powder and 0.3kg of water reducing agent were mixed evenly and put into a mold, pressed and cured to obtain a substrate.
[0035] Example 3 A method for preparing a composite aerogel insulation board comprises the following steps: S1. Specifically includes the following steps: S1-1, 40 kg of water and 20 kg of ethanol were mixed, and then 5 kg of sodium carboxymethyl cellulose was added, 8 kg of 1,3,5-triaminobenzene was added, and then 15 kg of polyvinyl alcohol, 10 kg of polyacrylamide, 20 kg of graphene oxide, 15 kg of PAMAM, 25 kg of carboxylated multi-walled carbon nanotubes, and 3 kg of genipin were added, and the mixture was stirred to obtain a modified solution; S1-2, immersing a 5 mm thick silica aerogel felt in a modified liquid at a temperature of 50°C, a immersion time of 40 min, and an immersion pressure of 2.5 MPa, then taking out the impregnated silica aerogel felt, and spreading glass fiber on one side of the silica aerogel felt, wherein the amount of the glass fiber is 5 wt% of the mass of the silica aerogel felt, and then drying and curing; S1-3, coating one side of the silica aerogel felt with glass fiber with an acrylic film, and then bonding and curing it with a 2 mm thick polyimide aerogel foam layer to obtain a composite aerogel felt; S2. The polyimide aerogel foam layer side of the composite aerogel felt is bonded and cured with the substrate by adhesive, and the silica aerogel felt side of the composite aerogel felt is bonded and cured with the metal plate by adhesive to form a composite aerogel insulation board, wherein the adhesive in step S2 is acrylic self-adhesive.
[0036] The substrate in step S2 is prepared by the following method: 60kg of water, 120kg of cement, 10kg of silica aerogel powder, 8kg of EVA emulsion, 8kg of acrylic emulsion, 15kg of expanded perlite, 30kg of sand, 5kg of glass fiber, 15kg of limestone powder and 0.5kg of water reducing agent were mixed evenly and put into a mold, pressed and cured to obtain a substrate.
[0037] Example 4 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 1, except that in step S1-2, the immersion treatment of the silica aerogel felt in the modifying liquid is carried out under normal pressure.
[0038] Example 5 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 1, except that the polyimide aerogel foam layer in step S1-3 is first immersed in an impregnation liquid, and then dried and bonded and cured with the side of the silica aerogel felt sprinkled with glass fiber according to the steps in step S1-3, wherein the impregnation liquid is prepared by mixing 8kg of the porous tin dioxide-wood ceramic powder composite particles prepared in Preparation Example 1, 3kg of polyetheretherketone particles, 4kg of sodium carboxymethyl cellulose and 25kg of water, and the impregnation liquid covers the polyimide aerogel foam layer.
[0039] Example 6 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 1, except that the polyimide aerogel foam layer in step S1-3 is first immersed in an impregnation liquid, and then dried and bonded and cured with the side of the silica aerogel felt sprinkled with glass fiber according to the steps in step S1-3, wherein the impregnation liquid is prepared by mixing 5kg of the porous tin dioxide-wood ceramic powder composite particles prepared in Preparation Example 2, 2kg of polyetheretherketone particles, 3kg of sodium carboxymethyl cellulose and 20kg of water, and the impregnation liquid covers the polyimide aerogel foam layer.
[0040] Example 7 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 1, except that the polyimide aerogel foam layer in step S1-3 is first immersed in an impregnation liquid, and then dried and bonded and cured with the side of the silica aerogel felt sprinkled with glass fiber according to the steps in step S1-3, wherein the impregnation liquid is prepared by mixing 10 kg of the porous tin dioxide-wood ceramic powder composite particles prepared in Preparation Example 3, 5 kg of polyetheretherketone particles, 5 kg of sodium carboxymethyl cellulose and 30 kg of water, and the impregnation liquid covers the polyimide aerogel foam layer.
[0041] Example 8 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 5, except that no polyetheretherketone particles are added to the impregnation liquid.
[0042] Example 9 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 5, except that the amount of polyetheretherketone particles added to the impregnation solution is 7 kg.
[0043] Example 10 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 5, except that porous tin dioxide-wood ceramic powder composite particles are not added to the impregnation solution.
[0044] Embodiment 11 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 5, except that an equal amount of porous tin dioxide-wood ceramic powder composite particles in the impregnation solution is replaced by porous tin dioxide.
[0045] Example 12 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 5, except that the porous tin dioxide-wood ceramic powder composite particles in the impregnation solution replace the tin dioxide powder in an equal amount.
[0046] Comparative Example 1 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 1, except that step S1-3 is not performed, the silica aerogel sprinkled with glass fibers is directly subjected to the operation in step S2, the side sprinkled with glass fibers is directly bonded and cured with a substrate by an adhesive, and the other side is directly bonded and cured with a metal plate by an adhesive.
[0047] Comparative Example 2 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 1, except that in step S1-2, glass fiber is not spread, and step S1-3 is directly carried out to bond and solidify with the polyimide aerogel foam layer.
[0048] Comparative Example 3 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 1, except that the silica aerogel in step S1-2 is not immersed in a modified liquid, but is directly coated with acrylic glue and then sprinkled with glass fiber, and then step S1-3 is directly performed to bond and fix with a polyimide aerogel foam layer to obtain a composite aerogel felt.
[0049] Comparative Example 4 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 1, except that 1,3,5-triaminobenzene is not added to the modified liquid in step S1-1.
[0050] Comparative Example 5 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 1, except that PAMAM is not added to the modified liquid in step S1-1.
[0051] Comparative Example 6 A method for preparing a composite aerogel insulation board is carried out according to the method in Example 1, except that no genipin is added to the modified liquid in step S1-1.
[0052] Performance Testing The thermal conductivity, compressive strength and flexural strength of the composite board after the composite aerogel felt and the cement gypsum substrate are bonded and fixed in step S1 of the present application embodiment and the comparative example are tested, and the test results are shown in Table 1 below: Table 1: Referring to the test results in Table 1 above, the thermal conductivity of the silica aerogel felt in the embodiment of the present application is 0.017W / (m·K), the compressive strength is 15MPa, and the flexural strength is 10MPa. Referring to the test results in Examples 1-3, it can be seen that when the composite board material in Examples 1-3 of the present application is made of silica aerogel felt impregnated in a modifying liquid and compounded with a polyimide aerogel foam layer, its thermal conductivity is further reduced, and it has better thermal insulation performance, and the compressive strength and flexural strength are significantly improved, and it has better mechanical properties. Combined with the test results of Example 4, when Example 4 is impregnated at normal pressure, its thermal insulation performance is slightly reduced, but its compressive strength and flexural strength are significantly reduced, and the mechanical properties are significantly reduced, which affects the formation of a cross-linked structure network in the composite structure.
[0053] Referring to the test results of Examples 5-7, when the polyimide aerogel foam layer is impregnated with the impregnation liquid, not only the thermal insulation performance is further reduced, but also its mechanical properties are further improved. Referring to the test results of Examples 8 and 9, when no polyetheretherketone is added to the impregnation liquid in Example 8, its thermal conductivity is slightly improved compared with Example 5, and the mechanical properties are significantly reduced. When the amount of polyetheretherketone added in Example 9 is too much, its thermal conductivity is increased, and the mechanical properties are improved. The effect of improving the mechanical properties is limited. Referring to Example 10, when no porous tin dioxide-wood ceramic powder composite particles are added, the thermal conductivity is significantly improved compared with Example 5, the thermal insulation performance is reduced, and the mechanical properties are significantly reduced. The addition of metal elements significantly improves the mechanical properties. When the composite particles are replaced with porous tin dioxide in Example 11, the mechanical properties are reduced instead. The addition of metal elements improves the mechanical properties, but the porous structure will reduce the mechanical properties. Combined with the test results in Example 12, when tin dioxide powder is added, the mechanical properties are better, but both the mechanical properties and the thermal insulation properties are weaker than those in Example 5.
[0054] Referring to the test results of Example 1 and Comparative Example 1, the thermal insulation and mechanical properties of the aerogel felt obtained by combining the silica aerogel with the polyimide aerogel foam layer in Comparative Example 1 are much lower than the comprehensive performance of the composite board in Example 1. Combined with the test results of Comparative Example 2, when glass fiber is not sprinkled between the silica aerogel felt and the polyimide aerogel in Comparative Example 2, the mechanical properties of the composite board are also significantly reduced. When the silica aerogel in Comparative Example 3 is directly compounded with the polyimide aerogel foam layer without being impregnated with the modifying liquid, its mechanical properties are also significantly weaker than those in Example 1. In the present application, when the silica aerogel felt is directly compounded with the polyimide aerogel foam layer without being modified, although the thermal insulation performance is improved, the mechanical properties are weak. Referring to the test results of Example 1 and Comparative Examples 4-6, it can be seen that when 1,3,5-triaminobenzene, PAMAM or genipin is not added to the modified liquid, the mechanical properties of the composite board are significantly reduced, and the thermal insulation performance is also reduced. This is mainly because the formation of a cross-linked structure can reduce the performance degradation problem caused by heat loss or thermal shrinkage.
[0055] Finally, the composite aerogel insulation board prepared in this application has excellent thermal insulation performance and better mechanical properties. In the construction field, especially in walls, roofs, floors and other parts, thermal insulation materials require a lower thermal conductivity to reduce heat transfer and improve the energy efficiency of buildings, or in refrigeration and freezing equipment, the use of low thermal conductivity materials can reduce energy loss and improve the efficiency of equipment. It has better application performance. Finally, the composite aerogel insulation board prepared in this application has better application effects in occasions requiring efficient thermal insulation, such as building exterior wall insulation, cold chain logistics, pipeline insulation, and thermal protection of aerospace vehicles.
[0056] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A composite aerogel insulation board, characterized in that: The invention comprises a substrate and metal plates arranged on both sides of the substrate, wherein a composite aerogel felt is arranged between the substrate and the metal plates, and the composite aerogel felt is prepared by the following method: The silica aerogel felt is immersed in a modified liquid, dried, and then sprinkled with glass fiber, and then bonded with a polyimide aerogel foam layer, wherein the polyimide aerogel foam layer is bonded to a substrate, and the silica aerogel felt is bonded to a metal plate; Among them, the modified liquid mainly includes graphene oxide, PAMAM, carboxylated multi-walled carbon nanotubes, 1,3,5-triaminobenzene and genipin.
2. A composite aerogel insulation board according to claim 1, characterized in that: The modified liquid comprises the following raw materials in parts by weight: 8-15 parts of polyvinyl alcohol, 5-10 parts of polyacrylamide, 30-40 parts of water, 10-20 parts of graphene oxide, 5-15 parts of PAMAM, 15-25 parts of carboxylated multi-walled carbon nanotubes, 3-8 parts of 1,3,5-triaminobenzene, 1-3 parts of genipin, 10-20 parts of ethanol and 2-5 parts of sodium carboxymethylcellulose.
3. The composite aerogel insulation board according to claim 1, characterized in that: When the silica aerogel felt is immersed in the modified liquid, the immersion temperature is 40-50° C., the immersion time is 40-60 min, and the immersion pressure is 1.2-2.5 MPa.
4. The composite aerogel insulation board according to claim 1, characterized in that: The thickness of the silica aerogel felt is 3-5 mm, and the thickness of the polyimide aerogel foam layer is 1-2 mm.
5. The composite aerogel insulation board according to claim 1, characterized in that: The polyimide aerogel foam layer is firstly immersed in an impregnation liquid, dried, and then composited with the silica aerogel felt. The impregnation liquid includes the following raw materials in parts by weight: 5-10 parts of porous tin dioxide-wood ceramic powder composite particles, 2-5 parts of polyetheretherketone particles, 3-5 parts of sodium carboxymethyl cellulose and 20-30 parts of water.
6. The composite aerogel insulation board according to claim 5, characterized in that: The porous tin dioxide-wood ceramic powder composite particles are prepared by the following method: Heat polycarbosilane and xylene in a water bath at 70-85°C, add wood powder after stirring, and then impregnate for 40-60 minutes under a vacuum condition of -0.09-(-0.1). After the impregnation, add porous tin dioxide, stir, and then heat to 150-170°C, keep warm for 20-30 minutes, then heat to 230-250°C, keep warm for 30-40 minutes and then cool to obtain porous tin dioxide-wood ceramic powder composite particles.
7. The composite aerogel insulation board according to claim 6, characterized in that: During the preparation of porous tin dioxide-wood ceramic powder composite particles, the amount of each raw material added is as follows: 10-20 parts of polycarbosilane, 15-25 parts of xylene, 10-20 parts of wood flour, 12-20 parts of porous tin dioxide.
8. The composite aerogel insulation board according to claim 1, characterized in that: The spreading amount of the glass fiber is 3-5wt% of the mass of the silica aerogel felt.
9. A method for preparing a composite aerogel insulation board according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, after the silica aerogel felt is immersed in a modified liquid, it is sprinkled with glass fiber, solidified, and then bonded and solidified with a polyimide aerogel foam layer to obtain a composite aerogel felt; S2. The polyimide aerogel foam layer side of the composite aerogel felt is bonded and cured with the substrate by adhesive, and the silica aerogel felt side of the composite aerogel felt is bonded and cured with the metal plate by adhesive to form a composite aerogel insulation board.
10. Application of the composite aerogel insulation board as claimed in any one of claims 1 to 8 in the fields of building exterior wall insulation, cold chain logistics, pipeline insulation and aerospace thermal protection.
Citation Information
Patent Citations
Polyimide foam / aerogel composite material and preparation method thereof
CN112358649A
High-strength aerogel modified heat insulation felt and preparation method thereof
CN112709075A
Lightweight thermal insulation composite board for building wall and processing technology of lightweight thermal insulation composite board
CN115142611A
Modified nano SiO2 aerogel and preparation method thereof
CN116393053A
Composite SiO2 aerogel material and preparation method thereof
CN117567923A